Cytotoxic and immunomodulatory properties of Tinospora cordifolia, Boerhaavia diffusa, Berberis aristata, and Ocimum basilicum extracts against HPV-positive cervical cancer cell line - Harsha Vaghasia; Rahul Patel; Jignesh Prajapati; Krupa Shah; Meenu Saraf; Rakesh M Rawal (BMC Complementary Medicine and Therapies)
Abstract Background Cervical cancer remains a significant public health concern, especially for low-and middle-income countries. This study explores the dual potential of medicinal plant extracts as both anticancer agents and immunomodulators, particularly in HPV-positive cervical cancer, while also addressing the limitations of conventional chemotherapy. Methods Extracts from Tinospora cordifolia, Boerhaavia diffusa, Berberis aristata, and Ocimum basilicum were tested on CaSki and HEK 293 cells alongside cisplatin. Cytotoxicity, genotoxicity, cell migration, HPV DNA inhibition, IFNG secretion, and cell cycle modulation were assessed using established biochemical and immunological assays, including qPCR, ELISA, and flow cytometry. Results Among the extracts, B. aristata demonstrated the strongest anticancer effects on cancer cells while exhibiting minimal impact on normal cells, highlighting its therapeutic potential. It also significantly reduced cell migration and has synergistic affect with cisplatin. B. diffusa emerged as the most effective in inhibiting HPV 16 DNA, suggesting its role in viral suppression. Immunomodulatory analysis revealed that T. cordifolia and O. basilicum significantly enhanced IFNG secretion, indicative of robust immune activation. Each tested extracts induced G0/G1 phase cell cycle arrest, with T. cordifolia showing the most pronounced effect. Conclusions This study highlights the novel therapeutic promise of integrating plant extracts into HPV-positive cervical cancer management. B. aristata stands out for its cytotoxicity and anti-migration properties, while T. cordifolia offers significant immunomodulatory benefits. These findings pave the way for further research into combining natural products with conventional therapies for safer, more effective cancer treatments.